2021
DOI: 10.48550/arxiv.2102.12474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Computational Advantage via High-Dimensional Gaussian Boson Sampling

Abhinav Deshpande,
Arthur Mehta,
Trevor Vincent
et al.

Abstract: Photonics is a promising platform for demonstrating quantum computational supremacy (QCS), the task of convincingly outperforming the most powerful classical supercomputers. Despite this promise, existing photonics proposals and demonstrations face significant hurdles. Experimentally, current implementations of Gaussian boson sampling lack programmability or have prohibitive loss rates. Theoretically, there is a comparative lack of rigorous evidence for the classical hardness of GBS. In this work, we make sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…The alterations to the Gray and Kourtis methodology introduced by Huang et al were later incorporated into the software library of Gray and Kourtis, CoTenGra [37]. In collaboration with NVIDIA, CoTenGra contracted a Sycamore-53 m = 20 sample in 558 seconds on the Selene GPU cluster [38] In [8] a three-dimensional random GBS quantum circuit containing 216 modes (6 modes per dimension of the circuit architecture) and a single cycle was proposed to showcase quantum advantage. In order to map the threedimensional random GBS circuit to a tensor-network simulation, a truncated Fock space corresponding to a qudit size of 4 was assumed.…”
Section: F Overview Of Previous Tensor-network Simulators For Quantum...mentioning
confidence: 99%
See 2 more Smart Citations
“…The alterations to the Gray and Kourtis methodology introduced by Huang et al were later incorporated into the software library of Gray and Kourtis, CoTenGra [37]. In collaboration with NVIDIA, CoTenGra contracted a Sycamore-53 m = 20 sample in 558 seconds on the Selene GPU cluster [38] In [8] a three-dimensional random GBS quantum circuit containing 216 modes (6 modes per dimension of the circuit architecture) and a single cycle was proposed to showcase quantum advantage. In order to map the threedimensional random GBS circuit to a tensor-network simulation, a truncated Fock space corresponding to a qudit size of 4 was assumed.…”
Section: F Overview Of Previous Tensor-network Simulators For Quantum...mentioning
confidence: 99%
“…In order to map the threedimensional random GBS circuit to a tensor-network simulation, a truncated Fock space corresponding to a qudit size of 4 was assumed. Using the theoretical compute performance of the Fugaku supercomputer, and the CoTen-Gra contraction path finder [3,37], Deshpande et al [8] found that the 6x6x6 circuit could be computed in ≈ 10 14 seconds assuming access to memory well beyond that of all the nodes of Fugaku together, let alone a single node of Fugaku. Slicing the circuit down to sizes that could fit in the 32GB RAM of a Fugaku node would come with a slicing overhead that was astronomical, making this circuit infeasible on current or future supercomputers.…”
Section: F Overview Of Previous Tensor-network Simulators For Quantum...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum computers operate in a multidimensional state space and are intrinsically probabilistic. They offer computational advantage for sampling tasks [28][29][30][31]. This was demonstrated experimentally with superconducting [32] and optical [33] quantum devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different approaches for demonstrating quantum advantage [4,5,6,7,8,9], photonics provides a promising track as it enables fast gate operations, room-temperature functioning and significant potential for scalability [10,11,12]. The most well-known and feasible photonic advantage scheme is Boson Sampling formulated by Aaronson and Arkhipov [4] and its extended variant known as Gaussian Boson Sampling (GBS) [13,14,15], which are shown to be classically intractable under certain assumptions [4,16]. However, it should also be mentioned that high loss rates, partial photon indistinguishably and other issues could make such systems classically simulable [17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%